Cover Feature: Heterogeneous Parahydrogen Pairwise Addition to Cyclopropane (ChemPhysChem 20/2018). Issue 20 (22nd October 2018) - Salnikov, Oleg G.; Kovtunov, Kirill V.; Nikolaou, Panayiotis; Kovtunova, Larisa M.; Bukhtiyarov, Valerii I.; Koptyug, Igor V.; Chekmenev, Eduard Y.
Abstract : The Cover Feature illustrates heterogeneous hydrogenation of cyclopropane with parahydrogen over Rh/TiO2 catalyst. Several spin states of propane with high level of proton nuclear spin polarization (i.e. hyperpolarized) are produced, and these hyperpolarized spin states can be used for MRI applications. The NMR‐invisible spin states (symbolized as the black hole) may potentially retain a hyperpolarized state for a very long time. More information can be found in the Communication by O. G. Salnikov et al. onpage 2621 in Issue 20, 2018 (DOI:10.1002/cphc.201800690 ).